The Digital Bureaucracy Paradox: The Dilemma of Visionary Leadership in Balancing Work From Anywhere (WFA) Flexibility and Civil Servant Discipline at the Regional Secretariat of Sorong City - Anace Fransiska Jitmau; Rini Werdiningsih; Permadi Mulajaya (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This research aims to conduct an in-depth analysis of the complex dynamics termed the